The Effect of Using Differentiated Instructional Strategy on Improving Reading Comprehension and Oral Expression of Students with Learning Disabilities - Al-Mashayek, Faten (Dirasat: Educational Sciences, 2022)
Objectives: The purpose of this study is to investigate the effect of using differentiated instructional strategy on improving the reading comprehension and oral expression of students with learning disabilities. The study sample included (38) male and female students from those who enrolled in the resource rooms of learning disabilities from third grade at the schools that belong to the southern al-Mazar directorate in the governorate of al-Karak. Methods: The participants were distributed in an intentional method into two groups: an experimental group that consisted of (18) students and a control group that consisted of (20) students. In order to achieve the objectives of study, the researcher designed an achievement test in reading comprehension based on three cognitive levels from the curriculum Arabic language of the third grade, as well as a scale for estimating oral expression based on five standard levels in oral expression Results: The results showed that there were statistically significant differences at the level (α = 0,05) in the performance of the students in the control and experimental groups on the post achievement test in reading comprehension in favor of the experimental group due to using the differentiated instructional strategy. There were statistically significant differences at the level (α = 0,05) in the performance of the students in the control and experimental groups regarding the scale of estimating the oral expression in favor of the experimental group due to using the differentiated instructional strategy. Conclusions: The study recommends, in light of its results, the necessity of conducting more studies on the differentiated education strategy using different age levels and variables, and testing the differentiated education strategy in teaching people with different disabilities with students without disabilities.